Polarization memory of photoluminescence related with Si nanoparticles embedded into oxide matrix - Michailovska, K.V.; Indutnyi, I.Z.; Kudryavtsev, O.O.; Sopinskyy, M.V.; Shepeliavyi, P.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Investigated in this paper have been polarization properties of photoluminescence in solid and porous nc-Si−SiOx light emitting structures passivated in HF vapor. These structures were produced by thermal vacuum evaporation of silicon monoxide SiO powder onto polished c-Si substrates. After annealing in vacuum for 15 min at the temperature 975 °C, SiOx films were decomposed to SiO₂ with Si nanoclusters embedded in the oxide matrix. Comparison of polarizations, inherent to exciting light and that of film photoluminescence, enabled to find the polarization memory effect in the passivated structures. In anisotropic porous nc-Si−SiOx samples, obtained by oblique deposition in vacuum, there is also well-defined orientation dependence of the PL polarization degree in the sample plane. This dependence is related to the orientation of oxide nanocolumns that form the structure of the porous layer. The above effects are associated with transformation during etching in HF the symmetric Si nanoparticles to asymmetric elongated ones.